Beta 2-adrenergic receptor gene association with overweight and asthma in children and adolescents and its relationship with physical fitness - Leite,Neiva (2015)
Objective: To investigate the association of Arg16Gly and Gln27Glu polymorphisms of β2-adrenergic receptor gene (ADRB2) with the occurrence of asthma and overweight and the gene's influence on anthropometric, clinic, biochemical and physical fitness variables in children and adolescents. Methods: Subjects were evaluated for allelic frequencies of the β2-adrenergic receptor gene, height, weight, body mass index (BMI), BMI Z-score, waist circumference (WC), pubertal stage, resting heart rate (HRres), blood pressure (BP), total cholesterol (TC), glucose, insulin, high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), triglyceride (TG), Homeostasis Metabolic Assessment (HOMA2-IR), Quantitative Insulin Sensitivity Check Index (QUICKI) and maximal oxygen uptake (VO2max). The participants were divided in four groups: overweight asthmatic (n=39), overweight non-asthmatic (n=115), normal weight asthmatic (n=12), and normal weight non-asthmatic (n=40). Results: Regarding the Gln27Glu polymorphism, higher total cholesterol was observed in usual genotype individuals than in genetic variant carriers (p=0.04). No evidence was found that the evaluated polymorphisms are influencing the physical fitness. The Arg16 allele was found more frequently among the normal weight asthmatic group when compared to the normal weight non-asthmatic group (p=0.02), and the Glu27 allele was more frequently found in the overweight asthmatics group when compared to the normal weight non-asthmatic group (p=0.03). Conclusions: The association of Arg16 allele with the occurrence of asthma and of the Glu27 allele with overweight asthmatic adolescents evidenced the contribution of the β2-adrenergic receptor gene to the development of obesity and asthma.